Violence against children/adolescents west of Santa Catarina - Hanauer, M. C.; Grasel, I.; Madureira, V. S. F. (Scientific Electronic Archives, 2020)
To characterize violence practiced against children and adolescents in the municipality of Santa Catarina. Exploratory-descriptive quantitative study, developed in a municipality in the west of Santa Catarina, from November 2011 to November 2012, collected data on the cases of violence filed at the Forum of the District of this municipality, totaling 1774 cases. Of the total analysis, 5% refers to violence against children and adolescents, sex crimes 25% female, offer / sell alcoholic beverages stood out age group of 11-15 years, aggressors highlighted male subjects 15-19 years, low level of schooling and no relationship to the victim, place of crime resided the victim’s residence and as to the outcome most crimes were filed. Violence often goes unnoticed in the eyes of society, leaving the victims unprotected. Within this expectation it can be evidenced that any type of violence has damages in the healthy development of children and adolescents, damaging periods of life that require more attention. Â